PENERAPAN STACK DAN QUEUE PADA ARRAY DAN LINKED LIST DALAM JAVA - Johnson Sihombing (POLITEKNIK PIKSI GANESHA, 2019)
In data structure programming, stack and queue are two types of non-primitive data structures of abstract data type that are used to store data elements both in arrays and in linked lists that are actually based on several events in real life. Stack uses the LIFO (last in first out) method to access and add data elements while the queue uses the FIFO (First in first out) method to access and add data elements. The study uses integer data types to be included in arrays and linked lists and tested against it by creating application programs using the Java programming language, which is a programming language with an object oriented concept. By using the JDK (Java Develompent Kit) version, the Java class to operate the linked list, queue and stack is available. To access data from these classes can be converted into an array or iterator (one-way list). Java already provides a LinkedList that is used as a queue, a Stack that is used as a stack, and ArrayDeque as a deque (a combination of queue and stack).